Internalisasi Nilai-Nilai Ajaran Agama Hindu, Dharma Agama, dan Dharma Negara di Banjar Tegal Sari, Desa Labuhan Badas, Sumbawa, Nusa Tenggara Barat - Ni Luh Drajati Ekaningtyas; Ni Putu Sasmika Dewi; Ni Made Ria Taurisia Armayani; Ni Ketut Windhi Maretha; Ni Made Arini (Perkumpulan Kualitama Edukatika Indonesia, 2022)
It is undeniable that access to quality education is not evenly distributed in all corners of Indonesia, including for religious education. Some areas still experience a scarcity of religious teachers, especially Hindu teachers and are still struggling with the problem of concerning levels of education. One of those areas is Banjar Tegal Sari, Labuhan Badas Village, Sumbawa, West Nusa Tenggara. This community service activity is carried out with counseling which aims to provide additional knowledge, skills, and positive attitudes about Hinduism, the importance of education for the younger generation, and how to carry out their role as good Hindus in religious, social, and state life. Counseling is carried out with materials and methods that are in accordance with the conditions and needs of the community, also adapted to the age group of the participants. The result of this community service is that all age groups gained a better understanding of Hinduism and its application in daily life as well as the importance of education for self-improvement. This result is the basis for the community to carry out the duty of their respective religions and the duty of their respective country.